Inheritance of Resistance to Bacterial Blight in Rice - Petpisit, V.; Khush, Gurdev S.; Kauffman, H.E. (Wiley, 1977)
The mode of inheritance and allelic relationships of the genes for resistance to bacterial blight, caused by Xanthomonas oryzae (Uyeda and Ishiyama) Dowson, in rice (Oryza sativa L.) cultivars ‘IR20’, ‘IR22’, and breeding lines ‘IR1529‐680‐3’, ‘IR1545‐284’, and ‘RP291‐7’ were studied. The study of F1, F2, F3 and reciprocal backcross populations of crosses between resistant parents and the susceptible cultivar ‘TNI’ revealed that resistance in these cultivars and selections is under monogenic control. The resistance of IR20, IR22 and IR1529‐680‐3 is incompletely dominant, and that of IR1545‐284 and RP291‐7 is recessive. Evidence from allele tests indicates that IR20, IR22 and IR1529‐680‐3 have the same dominant gene for resistance. This gene is designated Xa4. IR1545‐284 and RP291‐7 have the same recessive gene for resistance which is designated Xa5. Xa4 and xa5 assort independently of each other.